Efisiensi Dan Efektifitas Dengan Menggunakan Metode FIFO Dan FEFO Pada Obat Generik Tahun 2020-2021 - Ninik Fizziah Ummah; Yudi Siyamto (Nur Science Institute, 2022)
Drug inventory management is also very much needed because as a benchmark, where drug inventory management is said to be effective and efficient if it produces fast, precise and correct results. The purpose of this study was to determine the effectiveness and efficiency of generic drugs using the FIFO and FEFO methods. This type of research is quantitative with a descriptive method approach with a sample of 112 generic drug preparations used. The analysis used used drug inventory turnover ratio analysis and measured the level of effectiveness and efficiency of drug preparation management. The results show that the difference in the number of sales days with the company's standard of effectiveness and efficiency on generic drug products in 2020-2021 is declared effective and efficient with the value generated in 2020 of 66.07% and in 2021 of 70.54%, where the results this value is greater than the results of the calculation of the ineffective and efficient category, namely in 2020 it is 33,935 and in 2021 it is 29,46%